Gemcitabine plus erlotinib for advanced pancreatic cancer: a systematic review with meta-analysis. - Zu-Yao Yang; Jin-Qiu Yuan; Meng-Yang Di; Da-Yong Zheng; Jin-Zhang Chen; Hong Ding; Xin-Yin Wu; Ya-Fang Huang; Chen Mao; Jin-Ling Tang (PLoS ONE)
Background This study aims to comprehensively summarize the currently available evidences on the efficacy and safety of gemcitabine plus erlotinib for treating advanced pancreatic cancer. Methodology/principal findings PubMed, EMBASE, The Cochrane Library and abstracts of recent major conferences were systematically searched to identify relevant publications. Studies that were conducted in advanced pancreatic cancer patients treated with gemcitabine plus erlotinib (with or without comparison with gemcitabine alone) and reporting objective response rate, disease control rate, progression-free survival, time-to-progression, overall survival, 1-year survival rate and/or adverse events were included. Data on objective response rate, disease control rate, 1-year survival rate and adverse events rate, respectively, were combined mainly by using Meta-Analyst software with a random-effects model. Data on progression-free survival, time-to-progression and overall survival were summarized descriptively. Sixteen studies containing 1,308 advanced pancreatic cancer patients treated with gemcitabine plus erlotinib were included. The reported median progression-free survival (or time-to-progression), median overall survival, 1-year survival rates, objective response rates and disease control rates were 2-9.6 months, 5-12.5 months, 20%-51%, 0%-28.6% and 25.0%-83.3%, respectively. The weighted 1-year survival rate, objective response rate and disease control rate based on studies reporting robust results were 27.9%, 9.1% and 57.0%, respectively. According to the studies with relevant data, the incidences of total and severe adverse events were 96.3% and 62.9%, respectively. The most frequently reported adverse events were leucopenia, rash, diarrhea, vomitting, neutropenia, thrombocytopenia, anaemia, stomatitis, drug-induced liver injury, fatigue and fever. Compared with gemcitabine alone, the progression-free survival and overall survival with gemcitabine plus erlotinib were significantly longer, but there were also more deaths and interstitial lung disease-like syndrome related to this treatment. Conclusions/significance Gemcitabine plus erlotinib represent a new option for the treatment of advanced pancreatic cancer, with mild but clinically meaningful additive efficacy compared with gemcitabine alone. Its safety profile is generally acceptable, although careful management is needed for some specific adverse events.